The importance of design in lithium ion battery recycling – a critical review. Issue 22 (26th October 2020) - Thompson, Dana L.; Hartley, Jennifer M.; Lambert, Simon M.; Shiref, Muez; Harper, Gavin D. J.; Kendrick, Emma; Anderson, Paul; Ryder, Karl S.; Gaines, Linda; Abbott, Andrew P.
Abstract : Product design is an important factor which can control the efficiency and economics of a recycling flowsheet. Abstract : Recycling is always seen as an end-of-pipe process returning as much material as possible into a circular economy. There is a growing school of thought that suggests product design should be an important step in the recycling process. While this review is aimed specifically at one technological product, it contains facets that are applicable to the recycling of any complex product. Decarbonisation of energy production necessitates a proliferation of efficient electrical storage and a significant proportion of this, particularly in automotive propulsion, will use lithium ion batteries. The scale of the projected electric vehicle market means that a circular economy model needs to be established while the scale of end-of-life product is still manageable to prevent a build-up of hazardous waste. This critical review investigates the issues of lithium ion battery recycling and discusses the aspects of pack, module and cell design that can simplify battery dismantling and recycling. It highlights not only Green aspects of elemental recovery, but also technoeconomic features which may govern the appropriate direction for recycling. It also shows that as cell design changes, the approach to recycling can become more efficient.